Efficacy and the Safety of Granulocyte Colony-Stimulating Factor Treatment in Patients with Muscular Dystrophy: A Non-Randomized Clinical Trial - Sienkiewicz, Dorota; Kułak, Wojciech; Okurowska-Zawada, Bożena; Paszko-Patej, Grażyna; Wojtkowski, Janusz; Sochoń, Karolina; Kalinowska, Anna; Okulczyk, Kamila; Sienkiewicz, Jerzy; McEachern, Edward (Frontiers in Neurology, 2017)
Introduction: The current standard treatment for patients with Duchenne muscular dystrophy (DMD) involves corticosteroids. Granulocyte colony-stimulating factor (G-CSF) induces the proliferation of satellite cells and myoblasts and, in turn, muscle regeneration. Beneficial effects of G-CSF were also described for skeletal muscle disorders Aim: We assessed the safety and effects of using G-CSF to promote muscle strength in patients with DMD. Materials and methods: Inclusion criteria were: patients aged 5-15 years with diagnosed with DMD confirmed by genetic test or biopsy. Fourteen patients were treated with steroids and their use was not changed in this study. Diagnoses were confirmed by genetic tests: deletions were detected in 11 patients and duplications in 5 patients. Nineteen 5–15-year-old patients diagnosed with DMD—9 were in wheelchairs, whereas 10 were mobile and independent—completed an open study. Participants received a clinical examination and performed physiotherapeutic and laboratory tests to gauge their manual muscle strength, their isometric force using a hand dynamometer, and aerobic capacity (i.e., 6-min walk test) before and after therapy. Each participant received G-CSF (5 g/kg per body per day) subcutaneously for 5 consecutive days during the 1st, 2nd, 3rd. 6th and 12th month. Laboratory investigations which included full blood count and biochemistry were performed. Side effects of G-CSF treatment were assessed during each visit. During each cycle of G-CSF administration in the hospital, rehabilitation was also applied. All patients received regular ambulatory rehabilitation. Results: The subcutaneous administration of G-CSF improved muscle strength in participants. We recorded a significant increase in the distance covered in the 6-min walk test, either on foot or in a wheelchair, increased muscle force in isometric force, and a statistically significant decrease in the activity of the muscle enzyme creatine kinase after nearly every cycle of treatment. We observed no side effects of treatment with G-CSF. Conclusion: Our findings suggest that G-CSF increases muscle strength in patients with DMD, who demonstrated that G-CSF therapy is safe and easily tolerable. Keywords: granulocyte colony-stimulating factor, safety, efficacy, muscle strength, muscular dystrophy, children